EXISTENCE, UNIQUENESS AND STABILITY SOLUTIONS OF VOLTERRA INTEGRODIFFERENTIAL EQUATIONS WITH RETARDED ARGUMENT AND SYMMETRIC MATRICES - Raad Noori Butris; Sahla B Abdi (STMIK Pringsewu Lampung, 2021)
In this study, we investigate the existence, uniqueness, and stability solutions of Volterra integrodifferential equations with retarded argument and symmetric matrices. The Picard approximation method and Banach fixed point theorem have been used in this study. Theorems on the existence and uniqueness of a solution are established under some necessary and sufficient conditions on closed and bounded domains (compact spaces).